OPTIMASI FORMULA TABLET BUKAL MUKOADHESIVE GLIBENKLAMID MENGGUNAKAN MATRIKS CMC NA SERTA ASAM OLEAT SEBAGAI ENHANCHER - ASA FALAHI; DEWI RASHATI (JURNAL ILMIAH FARMASI AKADEMI FARMASI JEMBER, 2021)
Glibenclamide is a sulfonylurea class of antidiabetic drugs that works by stimulating insulin secretion in the pancreas so that it is effective only when the β-cells of the pancreas can still produce. The glibenclamide dosage form that is on the market is a conventional oral tablet which has various disadvantages in terms of pharmacokinetics. Based on this, it is necessary to develop a more effective drug delivery system for glibenclamide in order to avoid first-pass metabolism so as to increase the bioavailability of glibenclamide, namely by making mucoadhesive buccal tablets. This glibenclamide mucoadhesive buccal tablet is formulated using a variety of mucoadhesive polymers, namely CMC Na and oleic acid as enhancers. The manufacture of four mucoadhesive buccal tablet formulas used the direct compression method. The results of the weight uniformity test showed that they did not meet the NP requirements specified, all formulas had an NP of more than 15. The tablet hardness test also showed results that did not meet the test requirements. However, the results of the physical properties of the brittleness, pH and swelling index showed the results that met the test requirements. In this research, the optimum variation of CMC Na polymer and oleic acid as enhancers to physical properties (hardness, brittleness, pH, swelling ability) and the release of glibenclamide mucoadhesive tablets were CMC Na of 37.5 mg and oleic acid of 3.5. ml.